Computed tomography features for differentiating malignant and benign focal liver lesions in dogs: A meta-analysis. (December 2021) - Burti, S.; Zotti, A.; Contiero, B.; Banzato, T.
Highlights: A meta-analysis of the use of CT to characterise liver lesions in dogs was performed. The features used to distinguish benign from malignant lesions were analysed. Some qualitative CT features, when combined, had a sensitivity above 0.8. Some quantitative CT features, when combined, achieved statistical significance. Abstract: Computed tomography (CT) is often performed to complement ultrasound following detection of focal liver lesions (FLL). There is no consensus in the literature regarding the CT features that might be helpful in the distinction between benign and malignant FLL. The aim of this meta-analysis was to identify, based on the available literature, the qualitative and quantitative CT features able to distinguish between benign and malignant FLL. Studies on the diagnostic accuracy of CT in characterising FLL were searched in MEDLINE, Web of Science, and Scopus databases. Pooled sensitivity, pooled specificity, diagnostic odds ratio (DOR), receiver operator curve (ROC) area, were calculated for qualitative features. DOR were used to determine which qualitative features were most informative to detect malignancy; quantitative features were selected/identified based on standardised mean difference (SMD). Well-defined margins, presence of a capsule, abnormal lymph nodes, and heterogeneity in the arterial, portal and delayed phase were classified as informative qualitative CT features. The pooled sensitivity ranged from 0.630 (abnormal lymph nodes) to 0.786 (well-defined margins), while pooled specificity ranged from 0.643 (well-defined margins) to 0.816 (heterogeneous in delayed phase). Maximum dimensions, ellipsoid volume, attenuation of the liver in the pre-contrast phase, and attenuation of the liver in the arterial, portal, and delayed phase were found to be informative quantitative CT features. Larger maximum dimensions and volume (positive SMD), and lower attenuation values (negative SMD) were more associated with malignancy. This meta-analysis provides the evidence base for the interpreting CT imaging in the characterization of FLL.